2002
DOI: 10.1034/j.1399-6576.2002.460208.x
|View full text |Cite
|
Sign up to set email alerts
|

Accuracy of radial arterial pressure measurement during surgery under controlled hypotension

Abstract: Radial arterial pressure is an accurate measure of central arterial pressure during controlled hypotension achieved with arterial vasodilation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0
1

Year Published

2002
2002
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 21 publications
(31 reference statements)
1
7
0
1
Order By: Relevance
“…It was consistent with those studies in which vasodilating therapy was beneficial to artery pressure gradient [10,11]. Normally, SVRI is seldom determined by arteries located between aorta to radial arteries.…”
Section: Discussionsupporting
confidence: 91%
“…It was consistent with those studies in which vasodilating therapy was beneficial to artery pressure gradient [10,11]. Normally, SVRI is seldom determined by arteries located between aorta to radial arteries.…”
Section: Discussionsupporting
confidence: 91%
“…But other studies did not found the effect of these variables on arterial pressure gradients 22,23. Some studies have concluded that vasodilator therapy is beneficial in reducing arterial pressure gradients 24,25. Some studies have not found any significant effect of vasodilation or vasoconstriction of arterial pressure gradients 23,26.…”
Section: Discussionmentioning
confidence: 98%
“…Arterial catheterizations are an essential tool in monitoring hemodynamically unstable patients and taking repeated blood gas samplings . Due to its comparable accuracy, lower complication rate, and lower infection incidence, the radial artery is becoming accepted as the preferred vessel for arterial catheterization over the femoral artery . Despite a lower incidence of catheter‐related bloodstream infection in the radial artery compared to the femoral, catheters that remain in a patient for more than 4 days have comparable infection rates with central venous catheters .…”
Section: Discussionmentioning
confidence: 99%
“…23,24 In these reports, the emphasis was given on the catheterization of the femoral artery to monitor central blood pressure in order to effectively, accurately, and safely administer vasoactive drugs. 20 Other investigators demonstrate that peripheral blood pressure measurements are interchangeable with central blood pressure measurements in patients that are not critically ill. 6,25 The other primary consideration is the incidence and severity of complication from the catheterization of each artery. Once again, this is an issue of debate.…”
Section: Catheterization Of the Radial Arterymentioning
confidence: 99%